Learning-Styles According to the Model Hermann Quartrt (HBDI) of Eighth Grade basic Students - Muhammed Amir Abuzaed; Hamed Abdulla Salih (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Learning styles approach reinforces developing the suitable instructional materials for students. The current study aims to identify learning patterns according to the Herman model, in addition to identifying the most used and preferred learning styles of eighth grade high school students, the study was conducted on an eye consisting of (502) pupils and disciples of the eighth grade high school, in the schools of the Directorate of Education of the Arbil Center during the academic season 2021/2022, the research tool is a phrase of the questionnaire form consisting of (41) paragraphs, based on (likert scale) measure of five-dimensional Likert , distributed over (4) areas (external learning, interactive learning, procedural learning, internal learning) to confirm the sincerity and stability of the questionnaire was presented to a group of expert arbitrators and specialists, and used the descriptive approach with the use of computer statistical program (spss), and the following results were reached: Learning patterns of eighth grade secondary students at a high level, in the schools of the Education Directorate of the Arbil Center, the results of the hypotheses of the learning style according to the variable (gender) were not statistically significant.